Effects of Geometrical Parameters on Stress Wave Propagation across the Rough Joint - Chen Xin; Tan Wenhui; Wang Peng (Advances in Civil Engineering)
The contact surface of the rough joint has geometrical parameters as the joint matching coefficient (JMC) and the distribution pattern of the contact segments. The specimen used in the modified SHPB test got the artificial joint by sawing some notches on the surface contacted to the output bar. Different assemblies of the notches formed various contact areas and distribution patterns. Using the modified SHPB tests data, the altered thin-layer interface model was used to analyze the effects of geometrical parameters on one-dimensional stress wave transmission and energy dissipation across a single rough joint. It revealed that the transmission coefficient decreased with the diminution of JMC, and it increased with the scattered distribution pattern as the similar trend for each JMC set. As for the energy coefficients, with the decrease of JMC, the transmission energy coefficient reduced sharply, but it increased very slowly with the reflection energy coefficient and irreversible energy coefficient. It revealed that the JMC of 0.5 was the critical point of the energy dissipation. More energy transmitted across the joint rather than reflecting back and dissipating, when JMC > 0.5. Nevertheless, the irreversible energy coefficient was much larger than the transmission and reflection coefficients, when JMC < 0.5.